Pengaruh Penggunaan Model Pembelajaran Problem Solving Sistematis terhadap Hasil Belajar Fisika Dasar 2 Materi Listrik Arus Searah pada Mahasiswa Pendidikan Fisika - Tri Isti Hartini; Martin Martin (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2020)
This study aims to determine whether there is an effect of systematic problem solving learning models on basic physics learning outcomes 2. Based on the hypothesis proposed in this study, there is an effect of systematic problem solving learning models on basic physics learning outcomes 2. This research was conducted in the Physics Education Study Program. FKIP UHAMKA. The method used in this research is the experimental method. With the target population in this study were all students of the Physics Education Study Program FKIP UHAMKA, while the affordable population was semester 2 students. The sample was taken randomly (random sampling) by taking 20 students from semester 2 students. The design used in the study was one group pretest-posttest design. The data collection technique used a research instrument in the form of a written test (paper and pencil test), namely a description of 15 questions. Based on the hypothesis test using the t test, the t count was 2.78. While t table is obtained from table t with a significance level of α = 0.05 and degrees of freedom (dk) = 20, which is 1.725. Because tcount> ttable 2.78> 1.725, H0 is rejected. This H1 is accepted, which states that there is an effect of systematic problem solving learning models on student physics learning outcomes on direct current material.